An analysis of maslahah based resolutions issued by Bank Negara Malaysia - Haron, Razali; Eldersevi, Suheyib (Emerald Publishing Limited, 2019)
Purpose – This study aims to examine the resolutions issued by the Sharīʿah Advisory Council of Bank Negara Malaysia (SAC-BNM), which have recognized maslahah (public interest) as the basis of ruling to see the extent of its usefulness to the public and the extent of its adherence to the Maslahah parameters. The study will also look into the opposing opinion to identify the basis of rejection and overall implication on Islamic finance based on opposing opinions of SAC-BNM and other bodies of collective ijtihad (juristic interpretation). Design/methodology/approach – The study uses a qualitative approach by analyzing the SAC-BNM resolutions, which have been resolved based on Maslahah. The study also applies the comparative approach by comparing the fatwa (Sharīʿah pronouncement) issuing bodies of Malaysia and the Gulf Cooperation Council countries. Furthermore, the secondary data is obtained from sources such as usūl al-fiqh (theory of Islamic jurisprudence) books, papers and relevant internet sources. Findings – The study found that SAC-BNM’s resolutions are in line with some of the major Maslahah parameters mentioned in the usūl al-fiqh sources i.e. must not contradict with the Qurʾan and the Sunnah. While looking at the other two criteria of being in line with ijmaʿ (consensus) and having a general impact, such resolutions might not fulfill the criteria of valid Maslahah considering, respectively, the stand of collective ijtihad or the impact on the group of customers and institutions. Originality/value – Most available shari’ah (Islamic law) research considers the perspective of fiqh (Islamic jurisprudence) while analyzing the issue of Maslahah. This study aims to conduct analysis based on usūl al-fiqh. Moreover, Maslahah itself is a broad concept, which can be abused. Hence, this study discusses the parameters of Maslahah to understand the validity of an important juristic tool in Sharīʿah.